THE ROLES OF INDIVIDUAL COUNSELING SERVICES WITH HOME WORK ASSIGMENT TECHNIQUES TO REDUCE GADGET USE BEHAVIOR OF VOCATIONAL SCHOOL OF BINA PATRIA 1 SUKOHARJO IN 2020/2021 ACADEMIC YEAR - Nuke Virgia A.R; Hera Heru Sri Suryanti; Sri Hartini (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
The aim of the research is to find out how the role of individual counselling services using homework assessment techniques to reduce the behaviour of students using gadgets at SMK Bina Patria 1 Sukoharjo in the academic year 2020/2021. This research was conducted at SMK Bina Patria 1 Sukoharjo for the academic year 2020/2021. This research is a descriptive qualitative research, data collection techniques in this study using interviews, observations, documentation and home visits. In this study, the subject was one of the students of SMK Bina Patria 1 Sukoharjo for the academic year 2020/2021. The validity of the data used in this study was the triangulation of sources and data. Qualitative data analysis is inductive, which is based on an analysis of the data obtained, then a relationship pattern is developed with the following steps: data reduction, data presentation, results or conclusion. The results of this research is explain how the role of individual counselling services with homework assessment techniques to reduce the use of gadgets for students of SMK Bina Patria 1 Sukoharjo. From the results of individual counselling that was conducted for 4 (four) meetings, it was found that there was a change from the subject's self towards a better direction in excessive use of gadgets both at home, at school and in the community. It is hoped that participants can be responsible for themselves and the tasks given and realize that excessive use of gadgets will have a negative impact on their lives someday. Keywords: Individual Counselling Service with homework assessment techniques, use of gadgets.